Interventions and impact of pharmacist-delivered services in perioperative setting on clinically important outcomes: a systematic review and meta-analysis - Lina Naseralallah; Somaya Koraysh; Bodoor Aboujabal; May Alasmar (SAGE Publishing, 2024)
Background: The perioperative arena is a unique and challenging environment that requires coordination of the complex processes and involvement of the entire care team. Pharmacists' scope of practice has been evolving to be patient-centered and to expand to variety of settings including perioperative settings. Objectives: To critically appraise, synthesize, and present the available evidence of the characteristics and impact of pharmacist-led interventions on clinically important outcomes in the perioperative settings. Design: A systematic review and meta-analysis. Methods: We searched PubMed, Embase, and CINAHL from index inception to September 2023. Included studies compared the effectiveness of pharmacist-led interventions on clinically important outcomes (e.g. length of stay, readmission) compared to usual care in perioperative settings. Two independent reviewers extracted the data using the DEPICT-2 (Descriptive Elements of Pharmacist Intervention Characterization Tool) and undertook quality assessment using the Crowe Critical Appraisal (CCAT). A random-effect model was used to estimate the overall effect [odds ratio (OR) for dichotomous and standard mean difference (SMD) for continuous data] with 95% confidence intervals (CIs). Results: Twenty-five studies were eligible, 20 (80%) had uncontrolled study design. Most interventions were multicomponent and continuous over the perioperative period. The intervention components included clinical pharmacy services (e.g. medication management/optimization, medication reconciliation, discharge counseling) and education of healthcare professionals. While some studies provided a minor description in regards to the intervention development and processes, only one study reported a theoretical underpinning to intervention development. Pooled analyses showed a significant impact of pharmacist care compared to usual care on length of stay (11 studies; SMD −0.09; 95% CI −0.49 to −0.15) and all-cause readmissions (8 studies; OR 0.60; 95% CI 0.39-0.91). The majority of included studies ( n  = 21; 84%) were of moderate quality. Conclusion: Pharmacist-led interventions are effective at improving clinically important outcomes in the perioperative setting; however, most studies were of moderate quality. Studies lacked the utilization of theory to develop interventions; therefore, it is not clear whether theory-derived interventions are more effective than those without a theoretical element. Future research should prioritize the development and evaluation of multifaceted theory-informed pharmacist interventions that target the whole surgical care pathway.